A NEW OXYGEN-DEFICIENT PEROVSKITE PHASE CA(FE0.4SI0.6)O2.8 AND PHASE RELATIONS ALONG THE JOIN CASIO3-CAFEO2.5 AT TRANSITION ZONE CONDITIONS - Bläß U.W.; Langenhorst F.; Boffa-Ballaran T.; Seifert F.; Frost D.J.; McCammon C.A. (My University, 2004)
A new oxygen-deficient perovskite with the composition Ca(Fe0.4Si0.6)O2.8 has been synthesised at high-pressure and -temperature conditions relevant to the Earths transition zone using a multianvil apparatus. In contrast to pure CaSiO3 perovskite, this new phase is quenchable under ambient conditions. The diffraction pattern revealed strong intensities for pseudocubic reflections, but the true lattice is C-centred monoclinic with a=9.2486 , b=5.2596 , c=21.890 and =97.94. This lattice is only slightly distorted from rhombohedral symmetry. Electron-diffraction and high-resolution TEM images show that a well-ordered ten-layer superstructure is developed along the monoclinic c* direction, which corresponds to the pseudocubic [111] direction. This unique type of superstructure likely consists of an oxygen-deficient double layer with tetrahedrally coordinated silicon, alternating with eight octahedral layers of perovskite structure, which are one half each occupied by silicon and iron as indicated by Mssbauer and Si K electron energy loss spectroscopy. The maximum iron solubility in CaSiO3 perovskite is determined at 16 GPa to be 4 at% on the silicon site and it increases significantly above 20 GPa. The phase relations have been analysed along the join CaSiO3–CaFeO2.5, which revealed that no further defect perovskites are stable. An analogous phase exists in the aluminous system, with Ca(Al0.4Si0.6)O2.8 stoichiometry and diffraction patterns similar to that of Ca(Fe0.4Si0.6)O2.8. In addition, we discovered another defect perovskite with Ca(Al0.5Si0.5)O2.75 stoichiometry and an eight-layer superstructure most likely consisting of a tetrahedral double layer alternating with six octahedral layers. The potential occurrence of all three defect perovskites in the Earths interior is discussed.
Keywords: Calcium silicate perovskite; Oxygen vacancies; Stability; Trivalent cations; Transition zone